Spatio-temporal dynamics of jerky flow in high-entropy alloy at extremely low temperature - Pu, Z.; Xie, Z.C.; Sarmah, R.; Chen, Y.; Lu, Chunsheng; Ananthakrishna, G.; Dai, L.H. (TAYLOR & FRANCIS LTD, 2020)
© 2020 Informa UK Limited, trading as Taylor & Francis Group.